UNA PROPUESTA INTERPRETATIVA DEL OBJETO IMPUGNATORIO DE LA ADHESIÓN A LA APELACIÓN CONTRA SENTENCIA EN EL PROCESO CIVIL PERUANO - Yamunaqué Moreno, Kevin André (Revista de Derecho, 2022)
The article analyzed the characteristics, requirements and assumptions of adhering to the appeal against judgment in the Peruvian civil process, as well as its basis and the contradictory expressions of our legal system, along with some criticisms from the doctrine. With these ideas, it is possible to affirm the existence of an adhesion to the appeal with a broad objectionable object, for which a coherent interpretation of the procedural norms is proposed based on the indirect effect of suspension of the preclusive period caused by the appeal with respect to any decision. not appealed from the sentence. The objective of the study is to justify the existence of adhesion to the appeal as a resource with a broad challenging nature for practical purposes in the processes, which is developed under an explanatory methodology.
Keywords: intra-procedural appeals; adherence to appeal; target limit of adherence to appeal